Night of the living dummy II - Stine, R. L. (New York : Scholastic, 1995)
Amy's ventriloquist dummy, Dennis, keeps losing his head, so her dad buys Slappy from a local pawnshop to replace him, but horrible things start happening.
"An Apple paperback."
RL4.
008-012.
Accelerated Reader AR
Keywords: Puppets -- Fiction; Horror stories